Health personnel retention strategies in a peri-urban community: an exploratory study on Epworth, Zimbabwe - Taderera, Bernard Hope (Hum Resour Health, 2016)
BACKGROUND: The need to retain health personnel is a policy challenge undermining health system reform of the 21st century. The need to resolve this global health workforce crisis resulted in the First Global Forum on Human Resources for Health in 2008 from which the Kampala Declaration and Agenda for Global Action was formulated. However, whilst there have been several studies exploring the retention of health personnel towards this end, available literature does not provide a detailed narrative on strategies used in peri-urban communities. The aim of this study was to explore retention strategies implemented in a Zimbabwean peri-urban community between 2009 and 2014 and implications for peri-urban communities towards the health system reform agenda. METHODS: The study was carried out in Epworth, a peri-urban community in Harare, Zimbabwe. The research design was a cross-sectional survey, in which qualitative methods were used in sampling, data collection, reporting and analysis. Qualitative tools were used to collect data through in-depth interviews with purposively selected health personnel managers at 10 local clinics and sample interviews with purposively selected healthcare workers who included registered general nurses, state-certified nurses, midwives, environmental health technicians, nurse aids and community health volunteers at each clinic. Two focus group discussions were carried out with community health volunteers. Qualitative data was subjected to thematic analysis, with coding being performed manually. RESULTS: A programme-specific strategic partnership between the government and donor community contributed towards the mobilisation of more health personnel, health facilities, worker development and remuneration. To complement this, the Ministry of Health intervened through the review and payment of salaries, support towards post-basic training and development, and protection. The local board, mission and donors contributed through the payment of top-up allowances and provision of non-monetary incentives. CONCLUSIONS: The review of salaries, engagement of international strategic partners, payment of top-up allowances, support towards post-basic training and development, mobilisation of more health personnel, non-monetary incentives and healthcare worker protection were critical towards the retention of health personnel in the Epworth peri-urban community between 2009 and 2014.